2008
DOI: 10.1080/09500790802152175
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ongoing Strategic Behaviour of Students with Mild Mental Retardation: Implementation and Relations to Performance in a Problem-solving Situation

Abstract: The aim of this study was to investigate to what extent students with mild mental retardation exhibit strategic behaviour during problem solving and to investigate the relationships between the ongoing behaviours examined and the students' respective perfonnance. Eleven students with non-organic mild mental retardation participated in the study. Students were asked to perform the Block Design Cubes of the WISC-III and their problem-solving behaviour during task performance was video-recorded. For each particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
2
Order By: Relevance
“…They also have trouble focusing on the information needed for solving a particular problem (Scharnhorst & Buchel, 1995). People with mental retardation often are unable to solve problems involving the generalization of relationships (Dermitzaki, Stavroussi, Bandi, & Nisiotou, 2008), and therefore have difficulty transferring what they have learned regarding one situation to another.…”
Section: Prefacementioning
confidence: 99%
“…They also have trouble focusing on the information needed for solving a particular problem (Scharnhorst & Buchel, 1995). People with mental retardation often are unable to solve problems involving the generalization of relationships (Dermitzaki, Stavroussi, Bandi, & Nisiotou, 2008), and therefore have difficulty transferring what they have learned regarding one situation to another.…”
Section: Prefacementioning
confidence: 99%
“…A possible explanation could be that clients with relatively lower IQ scores do not experience as much negativity compared to clients with higher IQ scores. An explanation for this finding could be that a person with a relatively low IQ score has less ability to reflect on his/her own surrounding (Dermitzaki et al, 2008). Although there is still an ongoing discussion on whether people with MID are responsive to change in their environment, and earlier research suggests that people with lower IQs are less responsive to change in their environment (Van de Kamp, 2011; Zoon, 2013), our study showed that even participants with the lowest IQ score in our range (e.g., total IQ = 50) noticed a change in group climate.…”
Section: Discussionmentioning
confidence: 99%
“…Smatra se da je obrada informacija kod osoba sa IO manje rezultat svesnog, promišljenog čina, nego kod osoba tipičnog razvoja i da njihovo ponašanje u problem-situacijama često deluje automatski (Bebko & Luhaorg, 1998), a ponekad i nesistematično i dezorganizovano (Buha i Gligorović, 2012). Ograničena spontana upotreba i transfer strategija može biti odraz ograničenja u domenu bazičnih egzekutivnih funkcija, s obzirom na to da je odgovarajuće strateško ponašanje udruženo sa sposobnošću evaluacije zahteva i konteksta i sposobnošću kontrolisanja, nadgledanja i fleksibilne primene već naučenih strategija u novim situacijama (Dermitzaki et al, 2008).…”
unclassified